Six-band k · p approach to the effects of doping on energy dispersion in p-type strained In0.15Ga0.85As-Al0.33Ga0.67As quantum-well structures - W. Shi (2018)
We report an application of the six-band Luttinger-Kohn model to the subband energy dispersions in the valence band for the p-type In0.15Ga0.85As-Al0.33Ga0.67As quantum-well (QW) structures. It was found that, in addition to the conventional biaxial compressive strain related to the lattice constant and well width of the structures, the p-type doping also caused a shift of the subband energy levels in the valence band by varying the barrier height. It was also found that the strain of the QW structures was not a constant but was sensitive to the p-type doping intensity, which also induced the shift of the subband energy levels. The calculated results, based on intersubband transitions of the heavy holes and taking the doping-related changes in strain and barrier height into account, were in good agreement with the experimental data, measured using Fourier transform infrared technique.